Direct evidence of progressive cardiac dysfunction in a transgenic mouse model of Huntington’s disease - Wood, Nigel I. (2012)
The gene carrying the mutation causing Huntington’s disease (HD) is not brain specific, and there is increasing evidence for peripheral, as well as brain pathology in this disorder. Here, we used in vivo and ex vivo techniques to assess the cardiac function of mice transgenic for the HD mutation. Using magnetic resonance imaging (MRI) of the beating heart, we show that abnormalities previously reported in end-stage mice are present by the mid-stages of the disease. We also found abnormalities that have not been hitherto reported, including changes in cardiac efficiency and a mechanical distortion of the beating heart. Using the Langendorff preparation, we show reduced coronary blood flow, impaired myocardial contractility and reduced left ventricular developed pressure in HD mouse hearts. Together, our findings suggest that there is significant pathology of the HD mouse heart, even by the mid stages of disease. These are likely to contribute not only to the demise, but also to the progressive decline of the HD mouse. HD is characterised by cognitive as well as motor impairments. Given that previous clinical research has demonstrated that cardiac failure is a major risk factor for HD patients, and the risk of cognitive symptoms markedly increases in patients with heart failure, we suggest that closer attention should be paid to cardiovascular symptoms in HD patients.